Implicit overcompensation: The influence of negative self-instructions on performance of a self-paced motor task - de la Pena, D.; Murray, N. P.; Janelle, C. M. (Journal of Sports Sciences, 2008)
According to Wegner's (1994) theory of ironic processes of mental control, self-instructions not to perform in a certain way, together with mental loads, can induce thoughts, emotions, and behaviours that are precisely the opposite of intention. Wegner's theory was tested against the implicit overcompensation hypothesis, which states that movement direction and magnitude are implicitly dictated by self-instruction, irrespective of load, promoting overcompensation of action. Two experiments were conducted using a golf-putting task. In Experiment 1, 48 participants were randomly assigned to one of four load conditions: cognitive, visual, auditory, and self-presentation/incentive. In the experimental trials, participants were instructed to make the putt, but it was emphasized that the putt should not be left short of the target. Following the instructional strategy, putts landed significantly longer than at baseline, irrespective of load. In Experiment 2, 36 participants were divided into one of three groups, without load, in which different instructional sets (control, not putting long, and not putting short) were emphasized. A significant interaction emerged, as participants putted significantly longer or shorter than controls depending on the instructional set given. Overall, our findings support the implicit overcompensation hypothesis. Theoretical and practical considerations are discussed.